RESISTANSI AGAMA TERHADAP SAINS: FENOMENA MUSLIM INDONESIA PADA MASA PANDEMI - Asmawati Suwarno (UIN ANTASARI BANJARMASIN, 2022)
Abstract: This article aims to analyze science and religion in the context of a pandemic in Indonesia. The interesting thing as well as the topic of the problem in this article is how religion and science explain their role during the pandemic. More specifically, opposition to government policies will be clashed with the religiosity that most Indonesians believe in. Based on the literature study, the results obtained include an excessive understanding of religion that will make people increasingly distrustful of reality. During this pandemic, science and religion must complement each other, both of which are gifts from God. Science is considered as a human domination that is always colonized by worldly interests for people who only care about a vertical relationship to God. The scientific contribution of this article is to explain specifically where religion is the main factor in building community perspectives.Abstrak:Artikel ini bertujuan untuk menganalisis sains dan agama dalam konteks pandemi di Indonesia. Hal menarik sekaligus topik permasalahan dalam artikel ini adalah bagaimana agama dan sains menjelaskan perannya di masa pandemi. Lebih spesifiknya, penentangan terhadap kebijakan pemerintah akan berbenturan dengan religiositas yang diyakini sebagian besar masyarakat Indonesia. Berdasarkan studi literatur, hasil yang diperoleh antara lain pemahaman agama yang berlebihan yang akan membuat masyarakat semakin tidak percaya dengan kenyataan. Di masa pandemi ini, sains dan agama harus saling melengkapi, yang keduanya adalah anugerah dari Tuhan. Ilmu pengetahuan dianggap sebagai dominasi manusia yang selalu dijajah oleh kepentingan duniawi bagi orang-orang yang hanya mementingkan hubungan vertikal dengan Tuhan. Kontribusi ilmiah artikel ini adalah untuk menjelaskan secara spesifik dimana agama menjadi faktor utama dalam membangun cara pandang masyarakat